The Art of Writing an Effective Scientific Abstract: A Letter to the Editor - Akhtar Ebrahimi Ghassemi (Iran University of Medical Sciences, 2023)
The abstract is often the first text that people read before starting to read the entire article. Therefore, a great effort and attention should be paid in writing it. Since summarizing an article in a few sentences is difficult and requires professional skills, we aimed to address the importance and impact of an abstract and its function and types, and provide a practical guide to writing an effective and accessible scientific abstract.